Effect of Stabilization Splint Thickness on the Treatment Finding of Temporomandibular Disorders (Journal of Hama University, 2019)
Introduction: The stabilization splint has been used for many years as an effective treatment for Temporomandibular Disorders (TMD). However, The vertical separation between the maxillary and mandibular teeth in fabrication of the occlusal splint designed to achieve the maximum efficiency and muscle relaxation is controversial and undefined in the literature. So, The aim of this study is to evaluate the use of stabilization splint in the management of temporomandibular disorders (TMD), and to compare the efficacy of  2, 4 mm vertical thickness of stabilization splints.Materials and Methods: In this randomized clinical trial, 24 patients with TMD are diagnosed according to Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) and are randomly allocated into two groups (12 patients for each). Group 1: subjects are treated with 2 mm- thickness stabilization splint, Group 2: subjects are  treated with  4 mm- thickness stabilization splint for 3 months. Subjective pain according to visual analog scale (VAS) and objective maximum mouth opening were recorded at the delivery appointment , 1 month, 2 months, and 3 months after splint insertion. The changes in mean pain and maximum opening value by both splints at 1 month, 2 months, and 3 months in the two groups are analyzed with T student Independent Samples test.Results: The results of this study shows statistically significant improvement in pain levels and maximum mouth opening for the two groups at the end of the treatment, and the 4 mm- thickness stabilization splint is more effective than 2 mm- thickness stabilization splint on pain reduction.Conclusions: Within the limitations of this study it can be concluded that:Any one of the two stabilization splints (2 mm, 4 mm) is effective on the therapeutic management of temporomandibular disorders.The 4 mm-thickness stabilization splint is more effective only in pain reduction.